Environmental audit as a representative factor for organizations (Research, Society and Development, 2020)
Environmental Auditing is a recent technique in Brazil. This tool has become a part of everyday life, both in the search for certification, according to NBR ISO 14001 (2004), as well as the rigor imposed by environmental legislation, or even by requirements at the state level, to conduct environmental audits, assuming that the audit acts as an instrument in controlling compliance with policies, practices, procedures and / or requirements established in an attempt to reduce or even prevent environmental degradation. Given this context, the objective of this study is to analyze the process of implementation of an Environmental Audit, and what are the possible benefits for organizations. This is an exploratory study, using bibliographic and documentary research procedures, through the analysis of literature reviews related to the theme under study. The results showed that, among the benefits of environmental audits, the following can be enumerated: the commitment to the production process and the implementation of continuous improvements, induce the use of clean technologies, the efficient use of available resources (raw material), correct management. industrial waste, as well as the identification of potential hazards and risks, in addition to being linked to economic growth, the search for alternatives that propose sustainable development, since the Environmental Audit is not just another competitive differential.